LESBIAN GAY BISEXUAL TRANSGENDER (LGBT) SEBAGAI COSMOPOLITAN PARADOX LIFE STYLE DAN PENANGANANNYA MELALUI PENDIDIKAN TINGGI - Murry Darmoko (UIN Antasari Banjarmasin, 2018)
This study focuses on Lesbian Gay Bisexuals Transgender (LGBT) which are used as the cosmopolitan life style of today's generation. Evidence of social media shows the rapid development of LGBT members. In Shari'a through religious arguments, LGBT is haram and can be punished until the death penalty and also in LGBT health is considered as one of the causes of HIV-AIDS. However, sociologically, people can accept their presence. LGBT is a paradox of life style in the Muslim community of the world. LGBT is important to be studied, especially related to the pattern of Amar Ma'rûf Nahiy Munkar in Indonesia. Two formulation of the problem, How does the Amar Ma'rfu Pattern prevent LGBT? Second, How does the Nahiy Munkar Pattern overcome LGBT? The purpose of this study answers the two formulations above through Higher Education. Sociology of Law is used as a research approach with qualitative methods because it provides answers. The summary of the research results shows that higher education has a role in fostering LGBT through the socialization of MUI fatwa number 57 of 2014 and applying ant and bee patterns in implementing the Anti LGBT Campus Program through the teaching and learning process that explains LGBT in terms of religion and health and anti-campaign LGBT when implementing community service learning. Penelitian ini fokus pada Lesbian Gay Bisexual Transgender (LGBT) yang dijadikan sebagai kosmopolitan life style generasi masa kini. Bukti media sosial menunjukkan perkembangan pesat anggota LGBT. Secara syariat melalui dalil-dalil agama, LGBT adalah haram dan dapat dipidana sampai hukuman mati dan juga dalam kesehatan LGBT dianggap sebagai salah satu penyebab HIV-AIDS. Walaupun begitu, secara sosiologi, masyarakat dapat menerima kehadiran mereka. LGBT menjadi paradox life style dalam masyarakat muslim dunia. LGBT penting diteliti, terutama berkaitan dengan pola Amar Ma’rûf Nahiy Munkar di Indonesia. Dua rumusan masalah, Pola Amar Ma’rûf yang bagaimana dapat mencegah LGBT? Kedua, Pola Nahiy Munkar yang bagaimana dapat mengatasi LGBT? Tujuan penelitian ini menjawab dua rumusan di atas melalui Pendidikan Tinggi. Sosiologi Hukum dijadikan pendekatan penelitian dengan metode kualitatif karena memberikan jawaban. Ringkasan hasil penelitian menunjukkan pendidikan tinggi berperan dalam membina LGBT melalui sosialisasi Fatwa MUI nomor 57 tahun 2014 dan menerapkan pola semut dan lebah dalam melaksanakan Program Kampus Anti LGBT melalui proses belajar mengajar dengan kewajiban menempuh mata kuliah yang menjelaskan LGBT dari sisi agama dan kesehatan serta kampanye anti LGBT saat pelaksanaan KKN di masyarakat.